(untitled) (Communications in Mathematical Research, 2019)
In this paper, we study the homotopy category of unbounded complexes of strongly copure projective modules with bounded relative homologies K^∞,bscp(SCP). We show that the existence of a right recollement of K^∞,bscp(SCP) with respect to K^–,bscp(SCP), K_bscp(SCP) and K^∞,bscp(SCP) has the homotopy category of strongly copure projective acyclic complexes as a triangulated subcategory in some cases.